1989
DOI: 10.1128/iai.57.10.3123-3130.1989
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, sequence determination, and expression of a 32-kilodalton-protein gene of Mycobacterium tuberculosis

Abstract: We describe the identification of the gene encoding an immunodominant 32-kilodalton (kDa) protein of Mycobacterium tuberculosis. The 32-kDa antigen is abundantly secreted into the culture supernatant of a variety of mycobacteria and appears to be a major stimulant of cellular and humoral immunity against mycobacteria. Recombinant clones expressing a 140or 125-kDa j8-galactosidase fusion protein reactive with rabbit polyclonal anti-32 kDa protein serum were detected. The corresponding DNA sequence contains a 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
1

Year Published

1991
1991
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(48 citation statements)
references
References 33 publications
0
47
0
1
Order By: Relevance
“…The upstream region of the BCG 85A gene, from -274 to -251. was more A/T rich than ihe BCG 85A coding region (66.7% as opposed to 32.9%). Although Martine Borremans et al and Luk De Wit et al reported the sequence of 85A genes from M. tuberculosis and BCG, they did not contain this region [14,15]. The sequence of this region is similar to the E. coli CAP-binding site consensus sequence [40], The A/T rich regions were seen near the promoter region of several genes and were binding sites for transcription factors.…”
Section: Ykasdmentioning
confidence: 99%
See 1 more Smart Citation
“…The upstream region of the BCG 85A gene, from -274 to -251. was more A/T rich than ihe BCG 85A coding region (66.7% as opposed to 32.9%). Although Martine Borremans et al and Luk De Wit et al reported the sequence of 85A genes from M. tuberculosis and BCG, they did not contain this region [14,15]. The sequence of this region is similar to the E. coli CAP-binding site consensus sequence [40], The A/T rich regions were seen near the promoter region of several genes and were binding sites for transcription factors.…”
Section: Ykasdmentioning
confidence: 99%
“…The analogous gene was cloned recently from Mycobacterium leprae [12,13]. The genes for the 85A component were cloned from M. tubercuhm.s [14]. BCG [15], and M. leprae [16].…”
Section: Introductionmentioning
confidence: 99%
“…[54][55][56][57] Some of the more prominent antigens found in this fraction included the three members of the Ag85 complex (Rv3804c, Rv1886c, Rv0129c), plus Rv1196/PPE18, Rv0125/PepA, Rv0915c/PPE14 and Rv3616c. 58,59 In the lower molecular mass fraction, several proteins belonging to the ESAT-6 family (early secretory antigenic target-6) including ESAT-6/Rv3875, CFP10/ Rv3874, TB9.8/Rv0287 and Mtb9.9A/Rv1793 were isolated. [60][61][62][63] The ESAT-6 family was identified after the completion of the M. tuberculosis genome-this family is not based on homology among the members (which is quite limited) but rather on their organization on the bacterial chromosome where they are found as adjacent pairs close to a PPE or a PE gene.…”
Section: Antigen Discovery Prophylactic Vaccinesmentioning
confidence: 99%
“…Mycobacteria are Gram-positive bacteria, as is L. monocytogenes, but due to the highly complex, lipoid-rich cell wall structure of mycobacteria, the export machinery including signal-peptidase specificity may differ from L. monocytogenes. Yet, structural homology between BCG and Gram-positive bacterial signal peptide sequences has been reported [58,59]. The S. typhimurium aroA-strain belongs to the Gram-negative world as does E. coli.…”
Section: Improvement Of Bcg and S Typhimurium Aroaas Antigen Delivermentioning
confidence: 99%